A naked-eye biosensing system based on one-pot RPA-CRISPR/Cas12a driver G4-hemin self-assembly for Mycobacterium tuberculosis - Yuan, Ting; Yuan, Jianbo; Huang, Jian; Li, Nana; Cai, Huan; Yang, Yan; Li, Juan; Chen, Rui; Min, Xun (Frontiers in Chemistry, 2025)
IntroductionThe rapid and accurate identification of Mycobacterium tuberculosis (MTB) is essential for effective tuberculosis (TB) control. However, conventional diagnostic methods for MTB suffer from limitations such as low sensitivity, poor specificity, high cost, reliance on specialized instruments, and complex, time-consuming procedures. To address these challenges, there is an urgent need for a simple, rapid, and highly sensitive detection method that can be deployed in point-of-care settings.MethodsWe developed a one-pot biosensing system combining recombinase polymerase amplification (RPA) and CRISPR/Cas12a-driven G4-hemin self-assembly for the colorimetric detection of MTB. Glycerol was employed as a phase-separation barrier to prevent interference between RPA amplification and CRISPR/Cas12a trans-cleavage. A single-stranded DNA (ssDNA) probe, designed to self-assemble with ssDNA-hemin into G4-hemin nanozymes upon CRISPR/Cas12a-mediated cleavage, served as the reaction substrate. The ssDNA-hemin further enhanced the catalytic activity of the generated G4-hemin DNAzyme. The entire assay was completed in a single step within 60 min without requiring complex instrumentation.Results and DiscussionUnder optimized conditions, the biosensing system achieved ultrasensitive naked-eye detection of MTB with a limit of detection (LOD) of 10 copies/μL, comparable to traditional four-step fluorescent assays. Clinical validation using 104 patient samples demonstrated high concordance with standard diagnostic methods. This approach combines the advantages of recombinase polymerase amplification (RPA), CRISPR/Cas12a specificity, and G4-hemin DNAzyme-based colorimetric signal amplification, enabling simple, equipment-free visual detection. Given its speed, sensitivity, and ease of use, this biosensing system holds significant promise for point-of-care MTB nucleic acid testing in resource-limited settings.